Linguistic attitudes in Amazonian bilinguals - Falcón Ccenta, Pedro Manuel (2004)
The present study offers us the possibility of identifying the factors that condition the linguistic attitudes of two Peruvian Amazonian indigenous populations in order to understand, with greater objectivity, the value predisposition of indigenous users towards their own language and towards Spanish; their identification with their group and with the national society as a whole. It also allows us, in the first place, to evidence sociolinguistic and cultural elements conducive to outline a configuration of the scenario in which they develop their activities; secondly, to highlight the types of relationships they establish with indigenous members within their communities and with those who are not indigenous, both within and outside their communities.